Effects of the Sex Chromosome Complement, XX, XO, or XY, on the Transcriptome and Development of Mouse Oocytes During Follicular Growth - Yamazaki, Wataru; Badescu, Dunarel; Tan, Seang Lin; Ragoussis, Jiannis; Taketo, Teruko (Frontiers in Genetics, 2021)
The sex chromosome complement, XX or XY, determines sexual differentiation of the gonadal primordium into a testis or an ovary, which in turn directs differentiation of the germ cells into sperm and oocytes, respectively, in eutherian mammals. When the X monosomy or XY sex reversal occurs, XO and XY females exhibit subfertility and infertility in the mouse on the C57BL/6J genetic background, suggesting that functional germ cell differentiation requires the proper sex chromosome complement. Using these mouse models, we asked how the sex chromosome complement affects gene transcription in the oocytes during follicular growth. An oocyte accumulates cytoplasmic components such as mRNAs and proteins during follicular growth to support subsequent meiotic progression, fertilization, and early embryonic development without de novo transcription. However, how gene transcription is regulated during oocyte growth is not well understood. Our results revealed that XY oocytes became abnormal in chromatin configuration, mitochondria distribution, and de novo transcription compared to XX or XO oocytes near the end of growth phase. Therefore, we compared transcriptomes by RNA-sequencing among the XX, XO and XY oocytes of 50-60 µm in diameter, which were still morphologically comparable. The results showed that the X chromosome dosage limited the X-linked and autosomal gene transcript levels in XO oocytes whereas many genes were transcribed from the Y chromosome and made the transcriptome in XY oocytes closer to that in XX oocytes. We then compared the transcript levels of 3 X-linked, 3 Y-linked and 2 autosomal genes in the XX, XO and XY oocytes during the entire growth phase as well as at the end of growth phase using quantitative RT-PCR. The results indicated that the transcript levels of most genes increased with oocyte growth while largely maintaining the X chromosome dosage dependence. Near the end of growth phase, however, transcript levels of some X-linked genes did not increase in XY oocytes as much as XX or XO oocytes, rendering their levels much lower than those in XX oocytes. Thus, XY oocytes established a distinct transcriptome at the end of growth phase, which may be associated with abnormal chromatin configuration and mitochondria distribution.